Developing an ADDIE-Based TGTW Learning Model for Editorial Text Writing: An Evaluation of Its Validity, Practicality, and Effectiveness - Rahutami, Rahutami; Diana, L.N.; Wadji, Wadji; Himawan, Riswanda (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study aims to develop and evaluate the effectiveness of the TGTW (Team Game Tournament Writing) method in enhancing vocational high school students' ability to write editorial texts. It adopts a Research and Development (R&D) design based on the ADDIE model, followed by an effectiveness evaluation using a one-group pretest–posttest design involving 40 twelfth-grade vocational students. The data were analyzed using the Shapiro–Wilk test for normality, a paired-samples t-test, N-Gain analysis, and effect size calculation (Cohen's d). The validation results indicated a very high level of feasibility, with an average score of 94.66%. The effectiveness test revealed a statistically significant improvement between pretest (M = 61) and posttest (M = 85) scores (p < 0.05). The N-Gain value of 0.62 was categorized as moderate to high, while the effect size exceeded 2.0, indicating a very large impact. Beyond the statistical findings, the implementation of TGTW reflects key principles of the social constructivist paradigm, particularly through collaborative role distribution and the integration of prewriting and drafting processes within a structured group dynamic. Compared to prior studies on cooperative learning which typically report moderate effect sizes—this study demonstrates a notably stronger impact. Overall, these findings contribute to the advancement of collaborative, argument-based literacy models in vocational education. Future research is recommended to extend this work by employing more rigorous experimental designs, such as control-group comparisons, to further validate and generalize the results.